Zonal expression of StARD1 and oxidative stress in alcoholic-related liver disease - Raquel Fucho; Estel Solsona-Vilarrasa; Sandra Torres; Susana Nuñez; Naroa Insausti-Urkia; Albert Edo; Maria Calvo; Anna Bosch; Gemma Martin; Carlos Enrich; Carmen García-Ruiz; Jose C. Fernandez-Checa (Journal of Lipid Research, 2023)
Alcoholic-related liver disease (ALD) is one of the leading causes of chronic liver disease and morbidity. Unfortunately, the pathogenesis of ALD is still incompletely understood. StARD1 has emerged as a key player in other etiologies of chronic liver disease, and alcohol-induced liver injury exhibits zonal distribution. Here, we report that StARD1 is predominantly expressed in perivenous (PV) zone of liver sections from mice-fed chronic and acute-on-chronic ALD models compared to periportal (PP) area and is observed as early as 10 days of alcohol feeding. Ethanol and chemical hypoxia induced the expression of StARD1 in isolated primary mouse hepatocytes. The zonal-dependent expression of StARD1 resulted in the accumulation of cholesterol in mitochondria and increased lipid peroxidation in PV hepatocytes compared to PP hepatocytes, effects that were abrogated in PV hepatocytes upon hepatocyte-specific Stard1 KO mice. Transmission electron microscopy indicated differential glycogen and lipid droplets content between PP and PV areas, and alcohol feeding decreased glycogen content in both areas while increased lipid droplets content preferentially in PV zone. Moreover, transmission electron microscopy revealed that mitochondria from PV zone exhibited reduced length with respect to PP area, and alcohol feeding increased mitochondrial number, particularly, in PV zone. Extracellular flux analysis indicated lower maximal respiration and spared respiratory capacity in control PV hepatocytes that were reversed upon alcohol feeding. These findings reveal a differential morphology and functional activity of mitochondria between PP and PV hepatocytes following alcohol feeding and that StARD1 may play a key role in the zonal-dependent liver injury characteristic of ALD.